Lady of quality ebook - Heyer, Georgette (Regency Romances, 2008)
Georgette Heyer's Regency romance novels have charmed and delighted millions of readers. Her smart, independent heroines and dashing heroes brilliantly illuminate one of the most exciting and fascinating eras of English history, when drawing rooms sparkled with well-dressed nobility, and romantic intrigues ruled the day. The spirited and independent Miss Annis Wychwood is twenty-nine and well past the age for falling in love. But when Annis embroils herself in the affairs of a pretty runaway heiress, Miss Lucilla Carleton, she is destined to see a great deal of her fugitive's uncivil and high-handed guardian, Mr. Oliver Carleton. Befriending the wayward girl brings unexpected consequences, among them the conflicting emotions aroused by her guardian, who is quite the rudest man Annis has ever met... Praise for Georgette Heyer and Lady of Quality: "In this delectable Georgette Heyer novel, the lady of quality and her bit-of-a-rake swain are the ones on whom our eyes are fixed. They don't play us false. Miss Heyer is in top form...romantic, amusing, and full of tart-tongued comment on the mores of the time."—Publishers Weekly "A writer of great wit and style...I've read her books to ragged shreds."—Kate Fenton, Daily Telegraph "Set in Bath in the last years of the Regency, it has the authentic Heyer sparkle."—Woman's Journal